Semantic - pragmatic meaning of nature - Łapiński, Jacek L. (Studia Ecologiae et Bioethicae, 2008)
Semantic meaning of the term „nature” comes from the Latin word „nasci” - „to get born”, and Greek words „physis” and „arche”, the substance of the latter two terms is fully explained in the Latin dictionary of A. Forcellini (Klotius Latinitatis Lexicon, 4, Prati 1868, p. 231-232) and the Greek-English dictionary of H. G. Liddell and R. Scott (Greek-English Lexicon, The Clarendon Press, Oxford 1940, 1958, p. 1964-1965.). Pragmatic sense of the term “nature” depends on the context (physical, philosophical, ecological, anthropological, relative, etc.). It can be also analyzed from two different perspectives: static and dynamic, this situation leads to the triple opposition: natural versus artificial, nature versus culture and nature versus environment. Ultimately, in the pragmatic sense, nature is a category making sense only in relation to the human being. Nature is a set of meanings registered by the human being in his world. Nature is a result of human wisdom and gained knowledge in science, philosophy and so on. Over the whole history of human thinking the true substance of this term has been always variable - determined by various factors: historic periods, philosophical and social trends, religions, different scientific exploration strategies, etc.